The Art of Asking Questions - STANLEY LE BARON PAYNE (Princeton University Press, 2014)
IN THE FIRST PLACE, this little book was not written by an expert in semantics, not even by a specialist in question wording. The author is just a general practitioner in research. Having made more than my share of mistakes in phrasing issues for public consumption and feeling the need for a book on the subject, I found that it was necessary to write it myself. In the process, my respect for the semanticist has increased beyond words. He is smart enough to use symbols to represent his ideas, but I have been so foolish as to try to use words in talking about words. In the second place, this book is very limited in its subject matter. It discusses the wording of single questions almost exclusively. It hardly touches upon problems of question sequence or the overall matter of questionnaire design. It seemed difficult enough to deal with wording alone. Perhaps another book and another writer will cover these other subjects. Third, the reader will be disappointed if he expects to find here a set of definite rules or explicit directions. The art of asking questions is not likely ever to be reduced to easy formulas. As it stands, this book consists of some observations of human behavior, a few principles of wording, many exceptions to these principles, several unexplained oddities, and numerous unsolved dilemmas. It is undoubtedly richer on the how-not-to side than on the how-to side. For want of a better description, it might be thought of as a collection of possible considerations for question wording. Fourth, I happen to think that even a serious subject can be treated too seriously. Consequently, I have included some of the amusing and perhaps irrelevant ideas which occurred to me as I wrote. In other words, I have enjoyed writing this book. I hope you will enjoy reading it.